The Multidimensionality of Urban Space in Light of the New Economy - Miszczak, Katarzyna; Wrona, Aleksandra (Wielowymiarowość przestrzeni miejskiej w świetle nowej ekonomii, 2023)
The multidimensionality of urban space in light of the new economy seems complex. The aim of this research was to introduce the meaning of both ideas and emphasise their importance for urban development. The subject of the research were case studies of two European cities, Rotterdam (the Netherlands) and Wroclaw (Poland). The research methods were the literature review, benchmarking, and case study, which help to understand and explain the analysed problem and confront it with the case studies. It is essential to note that the same solutions may not be suitable for every case. However, there are some urban policies and local governmental decisions that would be valuable good practices, which could solve challenges difficult for other urban units.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 74-83
Keywords: multidimensionality; urban space; new economy; urban development; Wroclaw; Rotterdam; wielowymiarowość; przestrzeń miejska; nowa ekonomia; rozwój miast; Wrocław